Circulating Tumor Cells in Patients With Colorectal Liver Metastasis Predict Impaired Survival. Issue 1 (January 2015) - Seeberg, Lars Thomas; Waage, Anne; Brunborg, Cathrine; Hugenschmidt, Harald; Renolen, Anne; Stav, Ingun; Bjørnbeth, Bjørn Atle; Brudvik, Kristoffer W.; Borgen, Elin F.; Naume, Bjørn; Wiedswang, Gro
<x xml:space="preserve">Abstract</x> Objective: The aim of the study is to assess the prognostic and predictive value of circulating tumor cells (CTCs) and disseminated tumor cells (DTCs) in bone marrow (BM) in patients with colorectal liver metastasis referred to surgery. Background: A total of 194 patients were included. Treatment of the patients was decided in a multidisciplinary team. Methods: BM aspirates and blood samples were collected at surgery, or in local anesthesia in nonresectable patients. CTCs were disclosed with CellSearch System, DTC with immunocytology. Results: Liver resection was completed in 153 patients. Forty-one patients were nonresectable, 22 preoperatively and 19 intraoperatively. The median follow-up was 22 (range 1–61) months. Relapse was diagnosed in 103 of the resected patients. Totally, 67 patients died of cancer. CTCs were detected in 19.6% of the patients. CTC positivity was significantly higher in nonresectable (46%) than in resectable patients (11.7%), P < 0.001. 13.8% of the patients had 2 or more CTCs, 31% of the nonresectable and 9.1% of the resectable patients (P = 0.001). Patients with 2 or more CTCs experienced reduced time to relapse/progression, both analyzing all patients (P = 0.002) and analyzing resectable patients (P < 0.001). Two or more CTCs was a strong predictor of progression and mortality in all subgroups of patients, together with more than 3 liver metastases, R1 resection, and extrahepatic disease. DTCs were detected in 9.9% of the patients, but not associated with clinical outcome in resectable patients. Conclusions: CTCs predict nonresectability and impaired survival. CTC analysis should be considered as a tool for decision-making before liver resection in these patients.